Reading-- from words to multiple texts - Britt, M. Anne.; Goldman, Susan R.; Rouet, Jean-François. (Routledge, 2013)
"Increasing the mastery of reading and text literacy in the general population is one of the most important challenges faced by both developed and developing societies. Providing a new reference for researchers and practitioners involved in this domain, this book brings together empirical research on the multiple levels of language that are involved in reading. It emphasizes the concrete outcomes of scientific research, and illustrates the continuity among levels. The chapters deal with clearly articulated questions, provide up to date reviews of the literature, and include discussions of the impacts of research outcomes for the practice of reading instruction. Furthermore, the volume addresses the gap between restricted and more functional approaches to reading competency. Finally, it addresses some of the new issues that arise from the rapid changes in reading practices that are related to the diffusion of digital technologies. Featuring contributions from authors who are among the acknowledged leaders in the field and presenting the state of the art and current controversies in reading and literacy research, this volume honors the profound impact of Charles Perfetti on reading research"--